The Analysis of Speech Acts in “English for Nusantara“ Textbook - Andrian Nuriza Johan; Januarius Mujiyanto; Sri Wuli Fitriati; Rudi Hartono (International Conference on Science, Education, and Technology, 2022)
In cross-cultural communication, pragmatic skill is extremely important. In pragmatics, speech acts are considered "one of the most convincing conceptions." It is strongly recommended that the textbook's materials include sufficient pragmatic components to enable learners to be pragmatically competent. The purpose of this study was to look at the speech acts in the textbook English for Nusantara . Qualitative research is used to collect data, analyze the data, and form a conclusion based on the analysis' findings. Content analysis is the type of qualitative study used. In an English text book titled English for Nusantara, data were speech acts in every utterance covered in each conversation. The finding was out of 191 data (utterances), there were 108 assertive/representative data, 49 directive data, 2 commissive data, 32 expressive data, and no declaration datum related to the categories of speech acts in the conversations in the textbook "English for Nusantara". The researcher found that these four types of speech act with their own functions were all existed in a hundred-eight utterances used by the speaker of each conversation in the textbook entitled English for Nusantara. For the functions of speech ach named assertive or representatives contained in the conversations of the textbook chosen by the researcher, there were stating, informing, and agreeing. Meanwhile, the function of speech act commissive that could be found were offering and promising. In the speech act type of directive , there could be found questioning and requesting. Last but not least, the functions of type of speech act expressive were thanking, complimenting, and expressing like.